Study of changes in phosphate, calcium and fluoride ions in plaque and saliva after the administration of a fluoride mouth rinse - Poureslami H; Torkzadeh M; Sefadini M (Wolters Kluwer Medknow Publications, 2007)
In this study, the effects of 0.2% sodium fluoride mouthwash solution on calcium, phosphate and fluoride ion contents of saliva and microbial plaque was assessed. Fourteen volunteer students (7-12 years of age) of a boarding educational centre in Kerman City (Iran) were selected and under defined conditions, their saliva and plaque samples were collected. The concentrations of fluoride, calcium and phosphate ions of the samples were determined, and after 14 days, under the same conditions, the students were asked to rinse their mouth with 0.2% sodium fluoride mouthwash solution. The second set of saliva and plaque samples were collected and the concentrations of the ions were determined. Data was analyzed using paired t-test and the results were presented as tables. P < 0.05 was considered as statistically significant. After using 0.2% sodium fluoride mouthwash solution, a significant increase was observed in the F 2 ion concentration both plaque ( P < 0.000) and saliva ( P < 0.000) of all the studied subjects, while the concentration of phosphate decreased in both saliva and plaque; however, this decrease was significant only in plaque ( P < 0.01). The calcium ion concentration decreased in both plaque and saliva; however, in none of them, the decrease was significant ( P >0.09 and P >0.2, respectively).